Nephrotic syndrome in young adolescent - Tee, Tat Khoo; Lim, Christopher Thiam Seong; Mohamad, Haidi; Mohamad Mokhtar, Elmina; Bak, Leong Goh (Malaysian Society Of Nephrology, 2024)
CASE PRESENTATION: A 13-year-old female presented with a one-week history of bilateral lower limb swelling associated with cough and sore throat. There was no fever, breathlessness, hematuria, or frothy urine. She denied connective tissue disease-related symptoms. There was also no family history of autoimmune disease or chronic kidney disease. On examination, her blood pressure was 135/91 mmHg with conjunctival pallor and lower limb pitting oedema. Her initial investigation showed haemoglobin of 9g/dL, LDH 390U/L, positive Coombs test with IgG 2+ and C3D 3+, and peripheral blood film showed spherocytes with no schistocytes or agglutination. Her creatinine was 40 μmol/L, urine protein 4+ blood 1+, 24-hour urinary protein of 7.4g/day and low albumin of 20g/dL. Her viral screening was non-reactive, and an immunology workup revealed negative ANA with normal C3 and C4 levels as well as negative ASOT.